Saúde mental de residentes de uma Universidade Pública do Paraná durante a pandemia de Covid-19 - Paetzold, Maira Gabriela (2021)
Students from healthcare residency programs are part of the front line in the fight against the new coronavirus pandemic, which can trigger or worsen depression, anxiety, and stress. Thus, the aim of this study was to analyze the mental health state of students in residency programs at a public university in Paraná, to know the associated factors of the studied population and propose ways to prevent mental disorders. To that end, a cross-sectional descriptive study was carried out through the application of a sociodemographic questionnaire and the Depression, Anxiety and Stress Scale – Short Form (DASS-21) in students of medical, multidisciplinary or in health professional area residency programs. To verify anxiety, depression, and stress scores in relation to sociodemographic data, a t-test was performed for two samples for variables with only two responses; and analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA) for variables with more than two responses. Statistical analyses were performed with 5% significance. Prevalence of stress and anxiety was 44.2% and, for depression, 38.5%. The associated factors were female gender, being a student from multidisciplinary and health professional area residency programs, drug use, fear of Covid-19 and having their family life directly affected by the pandemic. To help improve the mental health of professionals, we suggest certain activities to be conducted by the residency programs, such as psychotherapy, physical exercise, meditation, yoga, as well as pharmaceutical and psychiatric monitoring. These practices would reinforce the care of physical and mental health of residents, likely increasing their quality of life and consequently improving patient care.